Alveolar hemorrhage in systemic lupus erythematosus: a cohort review. (January 2016) - Andrade, C; Mendonça, T; Farinha, F; Correia, J; Marinho, A; Almeida, I; Vasconcelos, C
Diffuse alveolar hemorrhage (DAH) is a rare but potentially catastrophic manifestation with a high mortality. Among rheumatologic diseases, it occurs most frequently in patients with systemic lupus erythematosus (SLE) and systemic vasculitis. Despite new diagnostic tools and therapies, it remains a diagnostic and therapeutic challenge. The aim of this work was to characterize the SLE patients with an episode of alveolar hemorrhage followed in our Clinical Immunology Unit (CIU). A retrospective chart review was carried out for all patients with SLE followed in CIU between 1984 and the end of 2013. We reviewed the following data: demographic characteristics, clinical and laboratory data, radiologic investigations, histologic studies, treatment, and outcome. We identified 10 episodes of DAH, corresponding to seven patients, all female. These represent 1.6% of SLE patients followed in our Unit. The age at DAH attack was 42.75 ± 18.9 years. The average time between diagnosis of SLE and the onset of DAH was 7.1 years. Three patients had the diagnosis of SLE and the DAH attack at the same time. Disease activity according to SLEDAI was high, ranging from 15 to 41. All patients were treated with methylprednisolone, 37.5% cyclophosphamide and 28.6% plasmapheresis. The overall mortality rate was 28.6%.